PROFITABILITY OF THE TOURISM SUB-SECTOR: BEFORE, DURING AND AFTER THE COVID-19 - Endang Afriyeni; Jumyetti Jumyetti (Universitas Prof. Dr. Hazairin SH, 2025)
The purpose of this study was to assess the ability of tourism sub-sector companies listed on the Indonesia Stock Exchange to attain profits by utilizing all available capabilities and resources, including sales performance, asset utilization, and capital efficiency. The measurement period was before, during, and after the Covid-19. Using descriptive analysis methods. Using secondary data obtained from idx.co.id. The sampling technique was based on purposive sampling, resulting in 28 samples of tourism, hotel, and restaurant sub-sector companies listed on the Indonesia Stock Exchange. Profitability was measured using the profit margin ratio, ROA, and ROE. The results of this study prove that profitability before Covid-19 based on profit margin was better during the Covid-19 than before and after Covid-19. Meanwhile, based on ROA and ROE, it shows that the ability to manage company assets and capital showed better results after Covid-19 than the period before and during Covid-19. Losses during the pandemic were caused by decreased revenue in this tourism sector. The decrease in revenue occurred due to decreased hotel revenue, tour package revenue, vehicle rentals, and others. This study's limitations are that it only measures a company's ability to generate profits using all its capabilities and resources. This research is expected to provide insight into how the tourism sector survived and recovered from the crisis. This study compares three time periods, providing a more comprehensive view of the impact and recovery from the crisis.